Critical Discourse Analysis Online News “Omnibus Law” Job Creation Case (Teun A. Van Dijk Model) - Lisdwiana kurniati; Umi Kholidah; Novita Eka Tristiana (Universitas Muhammadiyah Semarang, 2023)
This research describes three aspects, namely, macro structure, superstructure, and micro structure of online news in Kompas, Detik, Sindo News, Republika, and Tribun omnibus job creation law. The purpose of this study was to describe the macro structure, superstructure, and microstructure of the online news discourse text of the omnibus law case. The methodological approach used in this research is descriptive qualitative, while the theoretical approach of TeunA. Van Dijk's Critical Discourse Analysis. Based on data analysis, the following results were obtained. First, critical discourse analysis of macro structure in online news, describes in general about the theme of